The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013 IEEE International Conference on Computer Vision 2013
DOI: 10.1109/iccv.2013.405
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Multi-resolution Surface Reconstruction from RGB-D Sequences

Abstract: We propose a method to generate highly detailed, textured 3D models of large environments from RGB-D sequences. Our system runs in real-time on a standard desktop PC with a state-of-the-art graphics card. To reduce the memory consumption, we fuse the acquired depth maps and colors in a multi-scale octree representation of a signed distance function. To estimate the camera poses, we construct a pose graph and use dense image alignment to determine the relative pose between pairs of frames. We add edges between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(84 citation statements)
references
References 21 publications
0
81
0
3
Order By: Relevance
“…The generation of the TSDFs f i : Ω 3 ⊂ R 3 → R follows related work [11,21,22,25]: given the i-th frame of range data D i : Ω 2 → R + together with the corresponding projection π i : R 3 → Ω 2 , the idea is to compute the signed distance φ i between the surface and each point x ∈ Ω 3 of the reconstruction volume along the line of sight. Furthermore, scaling with δ and truncation to [−1, +1] is performed to retrieve the final TSDF f i…”
Section: Tsdf-octree Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…The generation of the TSDFs f i : Ω 3 ⊂ R 3 → R follows related work [11,21,22,25]: given the i-th frame of range data D i : Ω 2 → R + together with the corresponding projection π i : R 3 → Ω 2 , the idea is to compute the signed distance φ i between the surface and each point x ∈ Ω 3 of the reconstruction volume along the line of sight. Furthermore, scaling with δ and truncation to [−1, +1] is performed to retrieve the final TSDF f i…”
Section: Tsdf-octree Generationmentioning
confidence: 99%
“…Octrees are established in many fields and are often used to alleviate computational burdens. Recent work ( [7,22,27]) uses Octrees for range data integration to map the environment, but employs simple update rules to encompass newly seen data without any optimization whatsoever. For simulation problems these partitioning structures are usually of static auxiliary nature (e.g.…”
Section: Arxiv:160807411v1 [Cscv] 26 Aug 2016mentioning
confidence: 99%
See 1 more Smart Citation
“…Common representations for 3D models include point clouds, surfels [10], triangle meshes [27], and signed distance functions [6]. Octrees allow for efficient data storage and fusion at multiple scales [9,24,28]. While KinectFusion [17] demonstrated that impressive 3D models can be acquired by tracking and fusing the depth images directly into a signed distance volume, drift will accumulate in the 3D model and inevitably lead to inconsistencies.…”
Section: Related Workmentioning
confidence: 99%
“…In order to overcome the size limit of the volumetric grid, moving volume approaches are adopted in [Roth and Vona 2012;Whelan et al 2012] to swap out voxels not in view of the depth camera from the graphics memory. In [Steinbrucker et al 2013], a multi-scale octree data structure and dense image alignment are adopted to reconstruct large-scale indoor scenes such as nine rooms along a corridor. Hierarchical spatial data structures and streaming algorithms are developed in [Chen et al 2013] to extend KinectFusion to large-scale scenes.…”
Section: Related Workmentioning
confidence: 99%